Pejabat Tanah Muar / Norhaliza Md Ibrahim - Md Ibrahim, Norhaliza (Faculty of Business and Management, 2023)
Industrial training benefitting the students to experience real life working environment because it provides preparation for future professional jobs. Students is able to learn significant skills with an invaluable perspective on the functioning of their chosen industry. Students will develop critical skills, such as problem-solving, communication, teamwork, and technical expertise. The real- life scenarios will challenge the student to adapt and apply their theoretical knowledge, thus reinforcing their learning that also contribute significantly to personal and professional growth. To put it simply, industrial training is a crucial component in preparing students for their future employment. It boosts their technical and soft skills while also giving them the experience they need to comprehend and deal with the challenges of the working world. Students who are taking part in an industrial training have the opportunity to enter the workforce with competence and confidence, my memorable and enlightening 6 months industrial training began at Muar District Land Office. This practical training offers me unique opportunity to witness and immerse myself in the real-world working environment. During my practical training, I gained some hands-on experience in various aspects of office administration and matters related to land administration. By participating in such training, it teaches me to be more well-equipped to enter the workforce with confidence and competence. In this industrial training report, it provides a comprehensive overview of SWOT analysis found by me in Muar Land Office and summarizes my profile, Muar Land Office’s background, vision and mission of the Muar Land Office, my training reflection, discussions of SWOT analysis and the conclusion.